2010
DOI: 10.1021/es103020e
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of PAHs in Aluminum Smelter Affected Sediments: Evaluation through Assessment of Pore Water Concentrations and in Vivo Bioaccumulation

Abstract: Bioaccumulation of polycyclic aromatic hydrocarbons (PAHs) from coal tar pitch polluted sediments was predicted by (1) a generic approach based on organic carbon-water partitioning and Gibbs linear free energy relationship (between K(OW) and K(OC)), and (2) measurements of freely dissolved concentrations of PAHs in the sediment pore water, using passive samplers and solid phase extraction. Results from these predictions were compared with those from in vivo bioaccumulation experiments using Nereis diversicolor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…PAHs emitted during the ferro-manganese plant activity in the Frierfjord and the electrode paste factory in Kristiansand may be entrapped in soot and coal particles during their formation, as previously pointed out (Allan et al, 2012;Arp et al, 2009;Jonker et al, 2005;Ruus et al, 2010). In addition, there have been discharges of Fig.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…PAHs emitted during the ferro-manganese plant activity in the Frierfjord and the electrode paste factory in Kristiansand may be entrapped in soot and coal particles during their formation, as previously pointed out (Allan et al, 2012;Arp et al, 2009;Jonker et al, 2005;Ruus et al, 2010). In addition, there have been discharges of Fig.…”
Section: Resultsmentioning
confidence: 68%
“…This explanation would also imply an equivalent metabolic capability in the gastropod (H. reticulata), considering the similar concentrations of accumulated compounds. Results by Ruus et al (2010), however, suggested that bioaccumulation in N. diversicolor and H. reticulata was highly influenced by the bioavailable fraction of compounds in sediment pore water, with metabolic capability of the species being less important. Allan et al (2012) emphasize that organic carbon/water partition coefficients for the three sediments in question were all high, and that simple predictive relationships (e.g.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…A passive sampler, such as silicone, low density polyethylene, or polyoxymethylene (Jonker and Koelmans 2001;Allan et al 2009), is then given time to equilibrate with the porewater of the sediment, and the porewater concentrations are estimated after extraction of the (solid phase) passive sampler. Earlier studies have indicated the importance of conducting such site-specific evaluations of porewater concentrations to accurately provide a basis for cost-effective risk assessment and remediation plans Arp et al 2009;Ruus et al 2010). …”
Section: The Sediment-to-water Partitioning Coefficient (K D )mentioning
confidence: 99%
“…Consequently, if there are indications of a problem with contaminated sediments, one usually ends up, in practice, performing Tier 3 risk assessments. Thorsen et al (2004), Arp et al (2009), andRuus et al (2010) have pointed out the importance of conducting site-specific evaluations of porewater concentrations and/or bioaccumulation studies by direct measurements in order to accurately provide a basis for risk assessment and remediation plans. Rust et al (2004) and Ruus et al (2010) also emphasized the importance of knowledge regarding the specific characteristics of the model organisms and species present in a threatened environment when predicting ecological risk of contaminated sediments.…”
Section: Bioconcentration Factor (Bcf Fisk )mentioning
confidence: 99%